Social workers and compassion - Collins, Stewart 1946- (Routledge Taylor & Francis Group, 2023)
Social Workers and Compassion is designed to assist social work students, social workers, social work managers, social care workers and lecturers in developing knowledge, understanding, skills and values related to various aspects of compassion. Drawing upon literature from social work, health care, social, organisational, work, and positive psychology, and from sociology and social policy from various parts of the world, the book will be of interest to international social work readers as well as professionals and professionals in training in the criminal justice, health care, counselling, and clinical psychology fields. It will be essential reading for social work students, lecturers, social care workers, social workers, and their managers"--